Active MgO-SiO2 hybrid material for organic dye removal: A mechanism and interaction study of the adsorption of C.I. Acid Blue 29 and C.I. Basic Blue 9. (15th December 2017) - Ciesielczyk, Filip; Bartczak, Przemysław; Zdarta, Jakub; Jesionowski, Teofil
Abstract: A comparative analysis was performed concerning the removal of two different organic dyes from model aqueous solution using an inorganic oxide adsorbent. The key element of the study concerns evaluation of the influence of the dyes' structure and their acid-base character on the efficiency of the adsorption process. The selection of sorbent material for this research – an MgO-SiO2 oxide system synthesized via a modified sol-gel route – is also not without significance. The relatively high porous structure parameters of this material (ABET = 642 m 2 /g, Vp = 1.11 mL and Sp = 9.8 nm) are a result of the proposed methodology for its synthesis. Both organic dyes (C.I. Acid Blue 29 and C.I. Basic Blue 9) were subjected to typical batch adsorption tests, including investigation of such process parameters as time, initial adsorbate concentration, adsorbent dose, pH and temperature. An attempt was also made to estimate the sorption capacity of the oxide material with respect to the analyzed organic dyes. To achieve the objectives of the research – determine the efficiency of adsorption – it was important to perform a thorough physicochemical analysis of the adsorbents (e.g. FTIR, elemental analysis and porous structure parameters). The results confirmed the significantly higher affinity of the basic dye to the oxide adsorbents compared with the acidic dye. The regeneration tests, which indirectly determine the nature of the adsorbent/adsorbate interactions, provide further evidence for this finding. On this basis, a probable mechanism of dyes adsorption on the MgO-SiO2 oxide adsorbent was proposed. Graphical abstract: Highlights: Synthesis and application of novel type hybrid adsorbent for organic dye removal. Comparative evaluation of removal of acid and basic dyes onto synthesized material. Comprehensive analysis of the adsorption process, including isotherms models. Mechanism and interaction study of adsorption process.